Proteomic analysis of plasma identifies the Toll-like receptor agonists S100A8/A9 as a novel possible marker for systemic sclerosis phenotype. Issue 8 (9th April 2014) - van Bon, L; Cossu, M; Loof, A; Gohar, F; Wittkowski, H; Vonk, M; Roth, J; van den Berg, W; van Heerde, W; Broen, J C A; Radstake, T R D J
Abstract : Background: Systemic sclerosis (SSc) is an autoimmune disease characterised by fibrosis of the skin and the internal organs. Except for anticentromere, antitopoisomerase I and antipolymerase III antibodies, there are no reliable circulating markers predicting susceptibility and internal organ complications. This study has exploited a proteome-wide profiling method with the aim to identify new markers to identify SSc phenotype. Method: 40 SSc patients were included for proteomic identification. Patients were stratified as having diffuse cutaneous SSc (dcSSc) (n=19) or limited cutaneous SSc (lcSSc) (n=21) according to the extent of skin involvement. As controls 19 healthy donors were included. Blood was drawn and plasma was stored before analysing with the SELDI-TOF-MS. For replication in serum, the cohort was extended with 60 SSc patients. Results: Proteomic analysis revealed a list of 25 masspeaks that were differentially expressed between SSc patients and healthy controls. One of the peaks was suggestive for S100A8, a masspeak we previously found in supernatant of plasmacytoid dendritic cells from SSc patients. Increased expression of S100A8/A9 in SSc patients was confirmed in replication cohort compared with controls. Intriguingly, S100A8/A9 was highest in patients with limited cutaneous SSc having lung fibrosis. Conclusions: S100A8/A9 was robustly found to be elevated in the circulation of SSc patients, suggesting its use as a biomarker for SSc lung disease and the need to further explore the role of TLR in SSc.